“Esquizofrenia”, produção do sofrimento e alteridade negada: análise crítica dos discursos da psiquiatria biológica - Maia, João Vitor Moreira (2020)
It is argued that suffering should be considered as a production, contrasting the conceptions that present it as something inherent, natural, to what in our society has been called mental illness; the idea of an even more striking suffering with regard to “Schizophrenia”. The thesis that the production of suffering is expressed as Denied Alterity is defended. By emphasizing the perspective of production, one understands the need to comprehend the relationship between subjectivity and culture in the constitution of subjects and the psychopathological phenomenon. In that sense, Michel Foucault’s critical thinking is referred to, by privileging his reflections on the historical process of the constitution of the psychopathological, psychiatric, and psychological fields, by highlighting the knowledge-power relationship in the forms of subjection, and the possibilities of resistance against the forms of subjectivation and submission. One seeks to approach the ethical-philosophical thinking of Emmanuel Lévinas, who in his reflections provokes us to open and welcome the Other in his essential difference, by effectively establishing a possibility of listening to others. The Biological Psychiatry discourses are critically analyzed about what is conventionally called schizophrenia, with the materiality of such discourses being obtained through the research and selection of works collected on the Health Virtual Library platform. The “Biological Psychiatry” and “Schizophrenia” categories were used, as well as the filter of works published since the beginning of the century, more precisely from 2001 to 2017, resulting in a total number of 83 studies, of which 76 were published in English, Spanish, and Portuguese. After reading them, 27 were selected to compose the materiality of the Biological Psychiatry discourses about “schizophrenia”. For the critical analysis of the Biological Psychiatry discourses about “schizophrenia”, an investigative path is elaborated to make explicit the possibility conditions for the emergence of the Biological Psychiatry discourse; the representations about “schizophrenia” formulated by such discourses; and also the “healing scenes” that are favored. The indications about suffering and “schizophrenia” are also analyzed in a transversal way; discursive strategies in the construction and consolidation of truth regimes; and an analysis of the effects of such discursive devices on the constitution of subjectivities. The effects of biological reductionism on the constitution of subjectivities are questioned, by analyzing the operation through which the subject of “schizophrenia” is represented in a totalizing way, and submitted to silence by the healing scene of antipsychotics, in which by concealing the human and political dimension of suffering, by favoring the admission of an eminently biological, cerebral, disciplined, meaningless subject. It is understood that the Critical exercise (in the Foucauldian sense of an indocility reflected before the truth regimes) and the Ethical exercise (in the Levinasian sense of knowledge criticism) favors the emergence of other forms of constitution of the subjects, and meaning of their experiences, being a necessary exercise before discourses in the psychopathological field.